2014
DOI: 10.1002/jppr.1024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy practice in Malaysia

Abstract: Background: The pharmacists' roles have been expanding around the globe in the recent years. In Malaysia, healthcare system is a two-tier system consisting of the public and private sectors. Pharmacy service in Malaysia came into existence in 1951 with the enactment of three main legislations governing its profession, namely, the Registration of Pharmacist Act 1951, Poison Act 1952 and Dangerous Drug Act 1952. However, the absence of dispensing right has limited the community pharmacists' professional roles to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Related to this, some pharmacists perceived that the absence of separation of dispensing and prescribing duties between private clinics and community pharmacies precluded them from applying the professional skills provided by their training. This issue has been mentioned previously in other pharmacy studies in Malaysia . Also consistent with a previous study, the significant relationship found in the present study between the number of prescriptions filled per day and job satisfaction supports the importance of patient contact as a source of job satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…Related to this, some pharmacists perceived that the absence of separation of dispensing and prescribing duties between private clinics and community pharmacies precluded them from applying the professional skills provided by their training. This issue has been mentioned previously in other pharmacy studies in Malaysia . Also consistent with a previous study, the significant relationship found in the present study between the number of prescriptions filled per day and job satisfaction supports the importance of patient contact as a source of job satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…The dispute over dispensing separation continues to dominate the Malaysian community pharmacy landscape, stifling further growth of existing pharmacy practice 43. Malaysian community pharmacists currently have exclusive jurisdiction over only a narrow range of pharmacy only medicine, which does not provide them sufficient competitive edge.…”
Section: Discussionmentioning
confidence: 99%
“…In the Malaysian context, the various challenges resulted in under-utilisation of community pharmacists’ clinical skills and knowledge 31. As the country’s healthcare system is in the precipice of a major overhaul, with a national health insurance scheme being considered to replace the current two-tiered public and private healthcare system, this study is timely to explore potential solutions to maximise the utilisation of their knowledge and skills for this purpose 31,32…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, although the role of the community pharmacist seems to be changing in many countries, 48.2% of physicians in Kuwait are still uncomfortable with pharmacists' suggestion about the use of prescription medications to patients. Furthermore, one third of physicians do not expect the pharmacist to be available for consultation during rounds [16,17]. Doctors and community pharmacists have little interaction in Libya and UAE, based on the findings of one particular study [18] which showed that almost 70 and 60% of doctors in Libya and UAE, respectively, either 'rarely' or 'never' discussed patients' drug therapy with a pharmacist.…”
Section: Statement Of the Problemmentioning
confidence: 99%